Acute nutritional stress during pregnancy affects placental efficiency, fetal growth and adult glucose homeostasis - Malik, S; Diot, A; Morten, K; Dombi, E; Vatish, M; Boyd, C; Poulton, J (Impact Journals, 2017)
Exposure to maternal malnutrition impairs postnatal health. Acute nutritional stress is less clearly implicated in intrauterine programming. We studied the effects of stressing pregnant mothers on perinatal growth and adult glucose homeostasis. We compared one group (“stressed”, mothers fasted for 16 hours) with controls (“unstressed”). We found that fasting stress had adverse effects on the reproductive success of the mothers (p =0.03), the weight of the fetuses conceived (p<0.005) and the placental efficiency (p<0.001) in stressed compared to unstressed offspring. Placental weight was increased (p<0.001) presumably in compensation. Stress affected the glucose homeostasis of the offspring when they became adults (p<0.005) when analysed as individuals. We previously linked nutritional stress throughout pregnancy with a mitochondrial stress response. We modelled placenta with cultured human trophoblast cells (BeWos) and fetal tissues with mouse embryonic fibroblasts (MEFs). High throughput imaging showed that the mitochondria of both cell types underwent a similar sequence of changes in morphology, induced by nutritional stresses. The contrasting stress responses on fetal and placental weight were not captured by the cellular models. The stress of maternal fasting may be an important determinant of perinatal outcome in the mouse and might be relevant to nutritional stress in human pregnancy.